2012
DOI: 10.1158/2159-8290.cd-11-0347
|View full text |Cite
|
Sign up to set email alerts
|

A Central Role for RAF→MEK→ERK Signaling in the Genesis of Pancreatic Ductal Adenocarcinoma

Abstract: KRAS mutation is a hallmark of pancreatic ductal adenocarcinoma (PDA), but remains an intractable pharmacological target. Consequently, defining RAS effector pathway(s) required for PDA initiation and maintenance is critical to improve treatment of this disease. Here we demonstrate that expression of BRAFV600E, but not PIK3CAH1047R, in the mouse pancreas leads to pancreatic intraepithelial neoplasia (PanIN) lesions. Moreover, concomitant expression of BRAFV600E and TP53R270H result in lethal PDA. We tested pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
249
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(263 citation statements)
references
References 26 publications
11
249
3
Order By: Relevance
“…36,37,[49][50][51] We found that at the serum-limiting conditions there was a significantly diminished activation of AKT in KRAS-dependent PDAC as assessed by Ser473 and Thr308-phosphorylation in the absence of HNRNPA2B1 (Fig 4, Fig S8). In contrast, and in agreement with the data above, HNRNPA2B1-depletion had no effect on AKT activation in KRAS-independent PDAC (Fig 4, Fig S8).…”
Section: Induction Of Apoptosis By Hnrnpa2b1 Downregulation In Kras-dmentioning
confidence: 79%
“…36,37,[49][50][51] We found that at the serum-limiting conditions there was a significantly diminished activation of AKT in KRAS-dependent PDAC as assessed by Ser473 and Thr308-phosphorylation in the absence of HNRNPA2B1 (Fig 4, Fig S8). In contrast, and in agreement with the data above, HNRNPA2B1-depletion had no effect on AKT activation in KRAS-independent PDAC (Fig 4, Fig S8).…”
Section: Induction Of Apoptosis By Hnrnpa2b1 Downregulation In Kras-dmentioning
confidence: 79%
“…Moreover, oncogenic BRAF mutations are mutually exclusive with KRAS mutations and are present in >30% of the KRAS wild-type PDAC cases (Witkiewicz et al 2015). Genetic studies in autochthonous models further showed that oncogenic Braf is sufficient to induce PDAC development (Collisson et al 2012), consistent with a strong epistatic relationship between oncogenic BRAF and KRAS mutations in PDAC and implicating the utility of BRAF inhibitors in PDAC. However it should be stressed that any clinical trial with RAF inhibitors should be restricted to patients with confirmed BRAF mutation, since targeting wildtype BRAF with RAF inhibitors can lead to paradoxical activation of ERK signaling through transactivation of CRAF (Poulikakos et al 2010) Together, these observations underscore the complex roles of cellular context in oncogenic KRAS signaling and the need for in-depth genetic analysis of the role and requirement of RAF/MEK/ MAPK pathway components in KRAS-driven PDAC genesis and tumor maintenance.…”
Section: Kras Signaling Surrogates In Tumor Development and Maintenancementioning
confidence: 88%
“…The MEK/ERK and the PI3K/mTOR cascade are prototypic survival pathways that have been implicated in tumorogenesis of NRAS mutant melanoma (9,21). Emerging preclinical evidence suggests that combined targeting of these two pathways with selective small-molecule inhibitors might be effective in treating malignancies with preexistent or acquired RAS mutations (22)(23)(24)(25). In this study, we demonstrate that MEKi combined with PI3K/mTOR 1,2 inhibition is able to synergistically reduce cell viability in vitro and decrease tumor size in vivo in a large panel of human NRAS mutant melanoma cells.…”
Section: Discussionmentioning
confidence: 99%